Hot deformation behavior and microstructure evolution of titanium alloy Ti-Al-Zr-Sn-Mo-Si-Y - 戚运连 奚正平 赵永庆 王蕊宁 杜宇 罗嫒媛 曾卫东 (Transactions of Nonferrous Metals Society of China, 2007)
Samples of Ti-Al-Zr-Sn-Mo-Si-Y alloy were compressed on the Gleeble-1500 heat stimulation machine. The compression test was carried out in the temperature range from 800 ℃ to 1 100℃ and strain rate range from 0.001 s^-1 to 10 s^-1. Stress-strain behavior and variation of microstructure of the alloy during hot compression were investigated. The experimental results show that the alloy is sensitive to temperature and strain rate, and the flow softening behavior is more obvious with the decrease of deformation temperature. At higher strain rate, discontinuous yielding is observed in β phase region. When deformed in α＋β phase region, with the increment of deformation temperature, the lamellar a structures globularization is more quick and more uniform. When deformed in β phase region, coarse β grains can be got because of high deformation temperature.